Law, language, and warfare - Crawford, Emily (Brill | Nijhoff, 2025)
"This volume presents a novel insight into the complex intersections between the law of armed conflict and the language of armed conflict. The work demonstrates the strengths and fissures in the law, showing how the choice to employ certain terms can have lasting ramifications for those most vulnerable to the impacts of warfare - civilians, women, children, and the displaced"--
Originally published, in part, as Volume 14, Issue 2 (2023) of Brill's journal Journal of International Humanitarian Legal Studies
Keywords: Information warfare (International law); Humanitarian law; Law / Language; Guerre de l'information (Droit international); Droit international humanitaire